The Multiannual Financial Framework and European Defence - Daniel Fiott (Intereconomics, 2018)
For the first time, security and defence will be a separate heading in the next MFF even though Article 41.2 of the Treaty on European Union (TEU) prohibits the use of the EU budget for defence reasons.
Keywords: 330